Vegetative anatomy and mycorrhizal morphology of Schoenorchis nivea (Lindl.) Schltr., (Orchidaceae) and their adaptive significance - Balachandar, Mayakrishnan; Ravi, Ravichandran Koshila; Nagaraj, Kandhasamy; Muthukumar, Thangavelu (Acta Biologica Szegediensis, 2019)
The anatomical description of the vegetative parts (leaf, leaf sheath, stem and root) and mycorrhizal morphology of Schoenorchis nivea (Lindl.) Schltr., belonging to the subfamily Epidendroideae of Orchidaceae was investigated. Leaves were amphistomatic covered by 10-12 μm thick cuticle, stomata paracytic with small and irregular substomatal chambers. Mesophyll homogenous, composed of thin-walled chlorenchymatous cells. Banded water-storage cells abundant in the mesophyll and the largest vascular bundle occurred at the centre of the leaf. The leaf sheath has both adaxial and abaxial epidermis covered with cuticle, homogenous mesophyll, water-storage cells, raphides and vascular bundles. The stem is surrounded by a uniseriate epidermis, cortex consisting of thick-walled fibers and collateral vascular bundles scattered in the ground tissue. Cortical proliferation was evident in S. nivea stem. Root hairs present in root regions were in contact with the substratum. Root hairs frequently branched at their tips. Root possess 2-3 layered velamen, ∩-thickened exodermal cells, O-thickened uniseriate endodermis, and cortex of thin-walled parenchymatous cells containing raphides and water-storage cells. Cover cells present. Xylem arches are 9-11, with vascular tissues embedded in sclerenchymatous cells. Pith composed of thick-walled sclerenchymatous cells with intercellular space. The stomatal characteristics in leaf, the size of water-storage cells and vascular bundles exhibited significant variation in different plant parts. Intact and degenerating pelotons of orchid mycorrhizal fungi were observed in the root cortical cells. The observations of the present study clearly indicate that S. nivea possesses several anatomical adaptations to thrive in epiphytic habitats.